Thiamine status, metabolism and application in dairy cows: a review. Issue 5 (10th July 2018) - Pan, Xiaohua; Nan, Xuemei; Yang, Liang; Jiang, Linshu; Xiong, Benhai
Abstract: As the co-enzyme of pyruvate dehydrogenase and α -ketoglutarate dehydrogenase, thiamine plays a critical role in carbohydrate metabolism in dairy cows. Apart from feedstuff, microbial thiamine synthesis in the rumen is the main source for dairy cows. However, the amount of ruminal thiamine synthesis, which is influenced by dietary N levels and forage to concentrate ratio, varies greatly. Notably, when dairy cows are overfed high-grain diets, subacute ruminal acidosis (SARA) occurs and results in thiamine deficiency. Thiamine deficiency is characterised by decreased ruminal and blood thiamine concentrations and an increased blood thiamine pyrophosphate effect to >45 %. Thiamine deficiency caused by SARA is mainly related to the increased thiamine requirement during high grain feeding, decreased bacterial thiamine synthesis in the rumen, increased thiamine degradation by thiaminase, and decreased thiamine absorption by transporters. Interestingly, thiamine deficiency can be reversed by exogenous thiamine supplementation in the diet. Besides, thiamine supplementation has beneficial effects in dairy cows, such as increased milk and component production and attenuated SARA by improving rumen fermentation, balancing bacterial community and alleviating inflammatory response in the ruminal epithelium. However, there is no conclusive dietary thiamine recommendation for dairy cows, and the impacts of thiamine supplementation on protozoa, solid-attached bacteria, rumen wall-adherent bacteria and nutrient metabolism in dairy cows are still unclear. This knowledge is critical to understand thiamine status and function in dairy cows. Overall, the present review described the current state of knowledge on thiamine nutrition in dairy cows and the major problems that must be addressed in future research.